The Inheritance and Development of Yang Qin Performance in Guangdong Colleges and Universities Under Multi-Cultural Background - Xu, Jia; Inkhong, Nutthan (วารสารนวัตกรรมการศึกษาและการวิจัย, 2026)
This Article aimed to study (1) the current situation of Yang Qin education in Guangdong colleges and universities is presented; (2) to analyze the opportunities and challenges brought by various factors to the Yang Qin cause in colleges and universities; and (3) to seize the opportunity and innovate the inheritance and development of Yang Qin education in colleges and universities under the multicultural background. This paper adopts qualitative and quantitative research methods to discuss the status quo, problems and challenges of the inheritance and development of Yang Qin in universities under the multicultural background. This paper adopts the case analysis method. The researchers took 16 colleges and universities with music colleges and music majors in Guangdong Province as the research objects to carry out thematic research. The results reveal significant issues including outdated curricula, insufficient course duration, lack of integration between theory and practice, limited teacher training, and poor infrastructure, all of which hinder students’ skill development and career readiness. Most institutions lack adequate teaching facilities and updated materials, with both teachers and students expressing dissatisfaction with available resources and learning environments. Market demand strongly influences students’ motivation to study Yang Qin, yet employment opportunities remain limited, underscoring the need for more diverse, modernized training that aligns with job market expectations. Additionally, teaching approaches often overlook students’ varied abilities, while emotional and creative aspects of performance are underemphasized. Opportunities for improvement lie in increasing professional course hours, enriching practical experience, enhancing teacher training, innovating teaching materials and methods, and strengthening alignment with market and societal needs. Under the influence of multicultural development, promoting Yang Qin education through scientific research, policy support, and expanded social visibility is essential for its sustainable inheritance and modernization.